PENGARUH PENERAPAN MODEL PEMBELAJARAN CONNECTING, ORGANIZING, REFLECTING, EXTENDING TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS PESERTA DIDIK KELAS XII SMA NEGERI 2 BATANG ANAI - Admizona, Titi Fitri (Jurnal Edukasi dan Penelitian Matematika, 2024)
Students are required to demonstrate proficiency in mathematical communication. Currently, this ability is still considered lacking in class XII of SMA Negeri 2 Batang Anai FY 2024/2025. Inactive learning and inappropriate models are the root causes of this lack of competence. There are many ways it can be used, one of which is using the CORE model which stands for Connecting, Organising, Reflecting, and Extending. This research is a quasi-experimental with posttest only control group. After analysing the data and evaluating the hypothesis, it was proven that students using the CORE model had superior results compared to the conventional method. In addition, the final test scores obtained during the implementation of the CORE model showed significant improvement.Keywords– Mathematical Communication Skills, Connecting, Organizing, Reflecting, Extending Learning, Conventional Learning Model